Design of tracking algorithms for spinning single-patch antenna GPS receivers - Wang Wenbin; Du Daocheng; Geng Shengqun (Dianzi Jishu Yingyong, 2019)
A GPS tracking algorithm is studied and applied to locate a spinning vehicle on which a single-patch antenna is mounted. This algorithm is able to track global positioning system(GPS) signals with intermittent availability at a lower rotational speed, but with enough accuracy to determine the rolling rate. Firstly, the received signals of single rolling antenna is analyzed and modeled. Then, based on the fact that the received signal has amplitude modulation information relative to the rolling characteristic, demodulation is performed using the symmetry of the rotational amplitude to detect the rolling rate and angle of the projectile. Actual test results show that，for using amplitude information of I/Q signals，rolling rate and rolling angle of spinning vehicle can be calculated in real-time by using proposed method，and calculation accuracy can meet requirements of most practical applications.